Relative train length and the infrastructure required to mitigate delays from operating combinations of normal and over-length freight trains on single-track railway lines in North America. (August 2019) - Dick, C Tyler; Atanassov, Ivan; Kippen, F Bradford; Mussanov, Darkhan
Distributed power locomotives have facilitated longer heavy-haul freight trains that improve the efficiency of railway operations. In North America, where the majority of mainlines are single track, the potential operational and economic advantages of long trains are limited by the inadequate length of many existing passing sidings (passing loops). To alleviate the challenge of operating trains that exceed the length of passing sidings, railways preserve the mainline capacity by extending passing sidings. However, industry practitioners rarely optimize the extent of infrastructure investment for the volume of over-length train traffic on a particular route. This paper investigates how different combinations of normal and over-length trains, and their relative lengths, relate to the number of siding extensions necessary to mitigate the delay performance of over-length train operation on a single-track rail corridor. The experiments used Rail Traffic Controller simulation software to determine train delay for various combinations of short and long train lengths under different directional distributions of a given daily railcar throughput volume. Simulation results suggest a relationship between the ratio of train lengths and the infrastructure expansion required to eliminate the delay introduced by operating over-length trains on the initial route. Over-length trains exhibit delay benefits from siding extensions while short trains are relatively insensitive to the expanded infrastructure. Assigning directional preference to over-length trains improves the overall average long-train delay at the expense of delay to short trains. These results will allow railway practitioners to make more informed decisions on the optimal incremental capital expansion strategy for the operation of over-length trains.